Social Media Marketing on Brand Awareness, Brand Preference and Brand Image: A Comparison of Facebook, X and Instagram - Laksamana, Patria; Iqbal, Muhammad; Maulani, Denia (Universitas Ibn Khladun Bogor, 2025)
This study aims to empirically explore the influence of social media marketing on three fundamental dimensions of brand equity—brand awareness, brand preference, and brand image—within the banking sector. Data were collected from users of three widely used social media platforms: Facebook, X, and Instagram. A total of 283 valid responses were obtained, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the hypothesized relationships. A structured questionnaire was developed to test all research hypotheses, and a non-probability convenience sampling technique was employed, primarily due to its practicality, ease of implementation, and efficiency in accessing a broad audience within a limited timeframe and budget. PLS-SEM was chosen for its robustness in analyzing complex models with latent constructs and its suitability for theory building. The path analysis confirmed that social media marketing exerts a positive and statistically significant influence on brand awareness, brand preference, and brand image. Furthermore, the platform-specific findings reveal that Instagram is the most effective channel for enhancing brand image, while X is more effective in improving brand awareness and brand preference. These insights provide practical value for marketing professionals by informing strategic decisions on platform selection and content prioritization in social media campaigns.